Urgensi Ratifikasi International Labour Organization 169 Sebagai Bentuk Perlindungan Hukum Terhadap Masyarakat Adat - Bandjar, Muhaimin Bahriansyah; Wattimena, Josina Augustina Yvonne; Leatemia, Wilshen (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Judging from the cases of indigenous peoples disputes, the efforts of the Indonesian state to speed up the ratification of ILO convention 169 will minimize the occurrence of cases that occur in indigenous peoples because there is protection for the indigenous peoples themselves. This situation prompted the development and adoption of ILO Convention 169, which aims to protect indigenous peoples and their rights.Purposes of the Research: This writing aims to examine and find out about ILO Convention 169 which regulates legal protection for indigenous peoples and why it is important for ILO Convention 169 to be ratified as a form of legal protection for indigenous peoples.Methods of the Research: The type of research used in this paper is normative legal research. As for answering the problems in this study, the authors use three approaches to the problem, namely the statutory approach (statute approach), and conceptual approach (conceptual approach). The procedure for collecting legal materials carried out by the author is by searching for and collecting laws and regulations related to the legal issues at hand. Legislation in this case includes both legislation and regulation. Analysis of legal material uses qualitative methods, namely studies related to legal norms contained in international law legislation and legal norms that exist in society.Results of the Research: The results of this study indicate that the ILO Convention 169 which regulates the legal protection of indigenous peoples, to ensure the implementation of the contents of this Convention, the responsibility lies in the hands of the government (ILO member ratifying ILO Convention No.169) to develop, coordinate and take systematic action in order protect the rights of Indigenous Peoples and Indigenous Peoples, and ensure recognition of their integrity. ILO Convention 169 is important to ratify as a form of legal protection for indigenous peoples and to strengthen the legal rights of Indigenous Peoples who mostly live in forest areas, the human rights of minorities are very difficult to be able to enjoy their rights on their own land.